Cardiovascular disease risk in women with premature ovarian insufficiency: A systematic review and meta-analysis. (January 2016) - Roeters van Lennep, Jeanine E; Heida, Karst Y; Bots, Michiel L; Hoek, Annemieke; ,
Aims: The purpose of this review was to assess the relationship between premature ovarian insufficiency (POI), defined as natural menopause <40 years, and risk of ischaemic heart disease (IHD), stroke and overall cardiovascular disease (CVD). Methods and results: We performed a systematic search in PubMed (1966–2012), EMBASE (1980–2012). Studies were included if they were prospective, follow-up>3 years, assessment of age menopause <40 years, and incident cases of fatal or nonfatal IHD, stroke, or overall CVD. Relative risks (RRs) and 95% confidence interval (CI) were pooled using a random-effect model. Overall, 10 observational studies were identified, comprising 190, 588 women (follow-up 4–37 years) with 9440 events (2026 events for IHD (seven studies) and 6438 events for stroke (seven studies) and 976 for total CVD (two studies). POI was assessed by questionnaire and incident cases through certification and event registers. POI was related to an increased risk of developing or dying from IHD (hazard ratio (HR) 1.69, 95% CI 1.29–2.21, p = 0.0001) and total CVD (HR 1.61, 95% CI 1.22–2.12, p = 0.0007). No relation was found for stroke (HR 1.03, 0.88–1.19, p = 0.74). We found no evidence for heterogeneity. Conclusion: POI is an independent though modest risk factor of IHD and overall CVD but not of stroke. Because of the limited impact of POI on CVD risk compared to classical cardiovascular risk factors, it is unlikely that POI will be implemented as modifier of cardiovascular risk classification.